Competence Level of B. Ed. First Year Students in Reading Comprehension - Timsina, Lok Nath (Educational Journal, 2023)
This study aims to explore the competence level of B.Ed. first year students in reading skill under Tribhuvan University. The data were collected by using two types of testing tools constructed from compulsory English text-book selecting two different reading passages. From the first, 14 objective questions were asked as multiple choice items which carried 14 marks; and from the other reading passage, 12 subjective questions were asked which carried 36 marks. The full mark of the test was fifty and the time allotted to conduct the test was an hour (60 minutes). Two campuses were the institutional samples and forty students from one and sixty students from the other were the samples for the study. Out of these hundred samples, 60 girls and 40 boys were selected proportionally. The marks obtained by the students in objective test item, subjective test item and total are the depended variables and the total number of students, the number of boys and girls are the independent variables. Through the study it was found that the students’ overall competence in reading comprehension was found around 50% in average. The reading competence they performed in objective test item was comparatively higher than subjective test item. In totality, the reading competence level of the boys was slightly better than the girls but the difference does not seem so significant.